The use of psychotropic drugs in Primary Care: medicalization in the Family Health Strategy in the context of the COVID-19 Pandemic (Research, Society and Development, 2023)
The COVID-19 pandemic was a global challenge for researchers, health managers and governments in the search for public health actions. to slow the rate of increase in contamination, with the aim of preventing the exhaustion of health systems and allowing the appropriate treatment of serious complications. The moment of a pandemic is sensitive regarding the impact of prescription and non-rational and even abusive use of medicines, and its implications extend beyond drugs used directly in the context of COVID-19, these factors are critical for the increase in medicalization. The pandemic crisis has favored the increase in cases of psychic suffering and mental disorders, with a potential impact on the prescriptions of psychotropic drugs. This study aims to analyze the use of medicalization in PHC in the context of the COVID-19 pandemic through an integrative review. Medicalization also delimits behavioral problems, which were not considered medical, but began to be treated pharmacologically, in the context of the COVID-19 pandemic, it was intensified mainly by the consumption of psychotropic drugs as a solution to the daily problems of the population that generate psychic suffering, acceptance of non-pharmacological approaches are infrequent and valued.